Large-Scale Gamma-Band Phase Synchronization and Selective Attention - Doesburg, Sam M.; Roggeveen, Alexa B.; Kitajo, Keiichi; Ward, Lawrence M. (Cerebral cortex (New York, N.Y. 1991), 2008)
Explaining the emergence of a coherent conscious percept and an intentional agent from the activity of distributed neurons is key to understanding how the brain produces higher cognitive processes. Gamma-band synchronization has been proposed to be a mechanism for the functional integration of neural populations that together form a transitory, large-scale, task- and/or percept-specific network. The operation of this mechanism in the context of attention orienting entails that cortical regions representing attended locations should show more gamma-band synchronization with other cortical areas than would those representing unattended locations. This increased synchronization should be apparent in the same time frame as that of the deployment of attention to a particular location. In order to observe this effect, we made electroencephalogram recordings while subjects attended to one side or the other of the visual field (which we confirmed by event-related potential analysis) and calculated phase-locking statistics between the signals recorded at relevant electrode pairs. We observed increased gamma-band phase synchronization between visual cortex contralateral to the attended location and other, widespread, cortical areas approximately 240–380 ms after the directional cue was presented, confirming the prediction of a large-scale gamma synchronous network oriented to the cued location.